2014
DOI: 10.1016/j.schres.2014.08.031
|View full text |Cite
|
Sign up to set email alerts
|

Low Vitamin D levels predict clinical features of schizophrenia

Abstract: Vitamin D plays crucial roles in neuroprotection and neurodevelopment, and low levels are commonly associated with schizophrenia. We considered if the association was spurious or causal by examining the association of Vitamin D with Leukocyte Telomere Length (LTL), a marker of cellular aging. Vitamin D levels in 22 well-characterized schizophrenia cases were examined with respect to symptoms, cognition, and functioning. LTL was assessed using quantitative polymerase chain reaction (qPCR). The results showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
2
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 25 publications
4
48
2
1
Order By: Relevance
“…Indeed, inadequate neurosteroid action of vitamin D on the brain, particularly during development, is related to the changes such as inflammatory and immunological disturbances, which are present in schizophrenia, too (49,50). Therefore, the cases of very low serum levels of 25(OH)D in our study probably point to patients with serious mental disorders that required the prescription of clozapine, the first line option for treatment-resistant psychotic features.…”
Section: Discussionmentioning
confidence: 72%
“…Indeed, inadequate neurosteroid action of vitamin D on the brain, particularly during development, is related to the changes such as inflammatory and immunological disturbances, which are present in schizophrenia, too (49,50). Therefore, the cases of very low serum levels of 25(OH)D in our study probably point to patients with serious mental disorders that required the prescription of clozapine, the first line option for treatment-resistant psychotic features.…”
Section: Discussionmentioning
confidence: 72%
“…Consistent with this finding, Groves et al (33) reported decreased levels of Glu and Gln in vitamin D‐deficient BALB/c mice. Dysfunction of the glutamate system in the prefrontal cortex is associated with schizophrenia, and that 1,25D apparently modulates Glu neurotransmission is suggestive of possible neuropsychiatric benefits of vitamin D centered on supporting GABA neurotransmission (34, 35).…”
Section: Discussionmentioning
confidence: 99%
“…17 Tengsl milli lágs styrks D-vítamíns í blóði og geðrofssjúkdóma hafa sést í rannsóknum og einhver teikn eru á lofti um að einkenni sjúkdómsins gaetu verið verri við lágan styrk. 18,19 Ein af þeim tilgát-um sem settar hafa verið fram til að útskýra þessar niðurstöður er að D-vítamín gegni mikilvaegu hlutverki við myndun á taugaboð-efninu serótónín, sem meðal annars tekur þátt í ferlum tengdum félagsfaerni og vitsmunagetu. 20 Einkenni geðrofssjúkdóma geta meðal annars falið í sér skerta vitsmunagetu og tilhneigingu til að draga sig í hlé félagslega.…”
Section: Umraeðaunclassified